Introduction to Chopper Machines as a Supporter of Increasing Production and Quality of Livestock Feed in Jember Jelbuk Village - Dwi Djumhariyanto; Mahros Darsin; Hari Arbiantara Basuki; Robertoes Koekoeh Koentjoro Wibowo (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
Silage is animal feed fermented to add nutrition and increase feed availability, especially during the dry season. The feed fermentation process is faster if the feed has been chopped before. This service aims to introduce choppers to Jelbuk Village, Jember Regency farmers. The service begins by discussing the problems faced by farmers/breeders, chaired by Mr. Mahfudz. They wanted a portable mini chopper to move and operate this machine at each member's residence. The chopper is modified from the previous multi-function chopper machine, which can chop leaves and twigs and crush animal manure for compost raw materials. Socialization of this machine is carried out simultaneously with training in making silage. After demonstrating the machine's operation and maintenance, the service partners were enthusiastic and rushed to try this new counter at their homes. They hope coaching activities can be continued later with the technologies they need.